Research of Electromagnetic Parameters of Sinusoidal Three-Phase Windings - Bukšnaitis, J. (Elektronika ir Elektrotechnika, 2007)
The distribution of the turns within section groups of the sinusoidal three-phase windings with maximum and average short-pitch are analyzed, for which pulsating or rotational magnetomotive forces can be optimized. Analytical expressions for evaluation of number of turns in the sections of windings of all four types were derived. On the basis of these expressions, there were calculated numbers of turns in relative quantities for sections, which form groups from two to four sections. These relative quantities are related to concentrated three-phase winding. Data table of magnetomotive force changes in the slots of considered sinusoidal three-phase windings in the moments of time t = 0 was formed and momentary dimensional stair-shape functions of rotational magnetomotive force were obtained according to this data. Real and conditional parameters of stair-shape half-periods were determined from the graphical representations of rotational magnetomotive force. On their basis the conditional amplitude values of dimensional harmonics of rotational magnetomotive force were found, which were used to evaluate analytically the conditional amplitude values of dimensional harmonics of rotating magnetomotive force. According to the data of conditional amplitude values the relative quantities of rotational magnetomotive force dimensional harmonics were found, which were later used to calculate magnetomotive force distortion and electromagnetic efficiency factors of considered three-phase windings. Winding factors of fundamental and higher harmonics were also determined according to the derived expression. Conclusions are offered on the basis of research of electromagnetic parameters of sinusoidal three-phase windings. Ill. 2, bibl. 6 (in Lithuanian; summaries in English, Russian and Lithuanian).